Analytical calculations of surges caused by direct lightning strike to underground intrusion detection system - K. Aniserowicz (Bulletin of the Polish Academy of Sciences: Technical Sciences, 2019)
The paper presents an analysis of overvoltages caused by a direct lightning strike in intrusion detection system equipped with underground radiating cable sensors. Waveforms of currents and voltages in the system components are calculated using analytical formulas basing on a transmission-line model in the frequency domain. The time-domain waveforms are computed using the inverse fast Fourier transform (IFFT). Three network configurations of the intrusion detection system are analyzed.